PERLINDUNGAN HUKUM DAN PENYELESAIAN JAMINAN FIDUSIA TERHADAP DEBITUR CIDERA JANJI - Ardini, Shela; Yahanan, Annalisa; Ridwan, Ridwan (Universitas Muhammadiyah Ponorogo, 2024)
A fiduciary guarantee is a form of guarantee or security in a financial transaction where a party called the debtor (the party who borrows) gives the right to a certain asset to the creditor (the party who provides the loan or credit) as collateral for the fulfillment of the debtor's obligations to the creditor. The aim of this research is to explore legal protection and settlement strategies in cases of fiduciary guarantees for debtors who default. This research uses a normative juridical writing approach supported by empirical evidence to identify and analyze the legal framework that regulates fiduciary guarantees in various jurisdictions, such as a statutory approach and a conceptual approach. This research also uses normative and empirical legal analysis methods. The results of the research show that the implementation of the legal protection given to creditors in a fiduciary guarantee agreement conforms to Law No. 42 of 1999 concerning Fiduciary Guarantees, namely by providing protection through the execution of fiduciary guarantees, and ultimately providing consideration of options for creditors and debtors to be able to take action negotiate first.